Global habitat predictions to inform spatiotemporal fisheries management: Initial steps within the framework - Heather D. Bowlby; Jean-Noël Druon; Jon Lopez; Maria José Juan-Jordá; María Teresa Carreón-Zapiain; Frederic Vandeperre; Agostino Leone; Brittany Finucci; Philippe S. Sabarros; Barbara A. Block; Haritz Arrizabalaga; Pedro Afonso; et al. (Marine Policy, 2024)

Trophic-Mediated Pelagic Habitat Structuring and Partitioning by Sympatric Elasmobranchs - André S. Afonso; Bruno C. L. Macena; Bruno Mourato; Natalia P. A. Bezerra; Sibele Mendonça; Joyce D. G. R. de Queiroz; Fábio H. V. Hazin (Frontiers in Marine Science, 2022)
Pelagic elasmobranchs are key elements of oceanic ecosystems and must be preserved if marine trophic networks are to be kept in balance. Yet, they face intense fishing pressure that has been threatening their populations worldwide. Ensuring proper conservation management of these taxa depends on a better understanding of the strategies they use to explore the pelagic realm and their contributions to trophic web structuring across the ocean column. This study aimed at examining relationships between vertical habitat use and trophic attributes among six sympatric pelagic elasmobranchs using satellite transmitting tags in the western equatorial South Atlantic Ocean. The vertical movements of 35 elasmobranch individuals were tracked during an overall total of 1911 days. Clear relationships between species’ feeding habits, maximum diving depths, and proportion of time spent either in epipelagic or in surface waters were evidenced by Bayesian generalized linear mixed models and multivariate analysis. Filter-feeders made most use of deep waters from the mesopelagic and bathypelagic and shifted their diving depths in phase with diel vertical migrations of the deep scattering layer, i.e., shallower during the night and deeper during the day. Specialists exhibited distinct diving patterns in epipelagic and mesopelagic waters across the diel period which are potentially indicative of habitat partitioning, whereas generalists were more surface-oriented but also explored deeper waters compared to specialists. The trophic level also seemed to influence elasmobranch maximum diving depths, which tended to become shallower as species’ trophic level increased. These results corroborate previous evidence of widespread vertical habitat partitioning among sympatric pelagic predators and depict a trophic-mediated structuring of the pelagic environment where top-down control may be exerted at different depths by distinct species. Further research is yet required to understand the role of elasmobranch vertical movements in structuring pelagic habitats as well as to guide ecosystem-based fisheries management aimed at reducing species susceptibility to fishing gear and at preserving the structure and functionality of marine trophic networks.

The importance of tangible and intangible factors in human–carnivore coexistence - Kim S. Jacobsen; Amy J. Dickman; David W. Macdonald; Susana Mourato; Paul Johnson; Lovemore Sibanda; Andrew Loveridge (Conservation Biology, 2021)
Conflict with humans is one of the major threats facing the world's remaining large carnivore populations, and understanding human attitudes is key to improving coexistence. We surveyed people living near Hwange National Park about their attitudes toward coexisting with lions. We used ordinal regression models with the results of the survey to investigate the importance of a range of tangible and intangible factors on attitudes. The variables investigated included the costs and benefits of wildlife presence, emotion, culture, religion, vulnerability, risk perception, notions of responsibility, and personal value orientations. This was for the purpose of effectively tailoring conservation efforts but also for ethical policy making. Intangible factors (e.g., fear and ecocentric values) were as important as, if not more important than, tangible factors (such as livestock losses) for understanding attitudes, based on the effect sizes of these variables. The degree to which participants’ fear of lions interfered with their daily activities was the most influential variable. The degree to which benefits accrue to households from the nearby protected area was also highly influential, as was number of livestock lost, number of dependents, ecocentric value orientation, and participation in conflict mitigation programs. Contrary to what is often assumed, metrics of livestock loss did not dominate attitudes to coexistence with lions. Furthermore, we found that socioeconomic variables may appear important when studied in isolation, but their effect may disappear when controlling for variables related to beliefs, perceptions, and past experiences. This raises questions about the widespread reliance on socioeconomic variables in the field of human–wildlife conflict and coexistence. To facilitate coexistence with large carnivores, we recommend measures that reduce fear (through education and through protective measures that reduce the need to be fearful), reduction of livestock losses, and ensuring local communities benefit from conservation. Ecocentric values also emerged as influential, highlighting the need to develop conservation initiatives tailored to local values.

Accounting for the Impact of Conservation on Human Well‐Being - E.J. MILNER‐GULLAND; J.A. MCGREGOR; M. AGARWALA; G. ATKINSON; P. BEVAN; T. CLEMENTS; T. DAW; K. HOMEWOOD; N. KUMPEL; J. LEWIS; S. MOURATO; B. PALMER FRY; et al. (Conservation Biology, 2014)
Conservationists are increasingly engaging with the concept of human well‐being to improve the design and evaluation of their interventions. Since the convening of the influential Sarkozy Commission in 2009, development researchers have been refining conceptualizations and frameworks to understand and measure human well‐being and are starting to converge on a common understanding of how best to do this. In conservation, the term human well‐being is in widespread use, but there is a need for guidance on operationalizing it to measure the impacts of conservation interventions on people. We present a framework for understanding human well‐being, which could be particularly useful in conservation. The framework includes 3 conditions; meeting needs, pursuing goals, and experiencing a satisfactory quality of life. We outline some of the complexities involved in evaluating the well‐being effects of conservation interventions, with the understanding that well‐being varies between people and over time and with the priorities of the evaluator. Key challenges for research into the well‐being impacts of conservation interventions include the need to build up a collection of case studies so as to draw out generalizable lessons; harness the potential of modern technology to support well‐being research; and contextualize evaluations of conservation impacts on well‐being spatially and temporally within the wider landscape of social change. Pathways through the smog of confusion around the term well‐being exist, and existing frameworks such as the Well‐being in Developing Countries approach can help conservationists negotiate the challenges of operationalizing the concept. Conservationists have the opportunity to benefit from the recent flurry of research in the development field so as to carry out more nuanced and locally relevant evaluations of the effects of their interventions on human well‐being. Consideración del Impacto de la Conservación sobre el Bienestar Humano

Oxidative stress induced by cadmium in Nicotiana tabacum L.: effects on growth parameters, oxidative damage and antioxidant responses in different plant parts - Luisa Louro Martins; Miguel Pedro Mourato; Ana Isabel Cardoso; Ana Paula Pinto; Ana Maria Mota; Maria de Lurdes S. Gonçalves; Amarilis de Varennes (Acta Physiologiae Plantarum, 2011)

Interannual variability of precipitation distribution patterns in Southern Portugal - S. Mourato; M. Moreira; J. Corte‐Real (International Journal of Climatology, 2010)
Southern Portugal is characterized by an irregular distribution of precipitation which is highly variable from year to year, requiring a clear ascertaining if the pattern of the precipitation is changing due to climate variability or climate change. In this paper, the authors applied several statistical methods to annual and seasonal time series of precipitation during the period 1931–2006, in order to detect trends and evaluate the variability in the frequencies of occurrence of dry and wet periods and also to assess spatial distribution patterns. The statistical methods include homogeneity tests, Mann–Kendall test, simple moving averages and cluster analysis. In spring, the authors detected a lack of homogeneity in the precipitation time series and a significant decreasing trend of precipitation was identified, by using simple moving averages and the Mann–Kendall test. Cluster analyses also confirmed the results and identified significant trends in the interannual and spatial distributions of dry, normal and wet years. It is concluded that the annual precipitation regime in the North interior sector is becoming drier, as the winter and spring also become drier. The only season in which a precipitation increase is observed is at fall and near the sea, but even for that region springs are also becoming drier. Copyright © 2009 Royal Meteorological Society

Effects of tryptamine on growth, ultrastructure, and oxidative stress of cyanobacteria and microalgae cultures - C. Churro; A. S. Fernandes; E. Alverca; F. Sam-Bento; S. Paulino; V. C. Figueira; A. J. Bento; S. Prabhakar; A. M. Lobo; L. L. Martins; M. P. Mourato; P. Pereira (Hydrobiologia, 2010)